Buenas prácticas para la gestión y conservación de la biodiversidad en ambientes litorales - Escudero Lozano, Pedro; Fernández Ramos, Julio; Martínez Arnal, Nerea; Monteagudo Albar, María; Sánchez Balibrea, Jorge; Zamora López, Antonio; BELMONTE SERRATO, FRANCISCO; Ballesteros Pelegrín, GUSTAVO ALFONSO; García-Marín, Ramón; Hernández Mármol, Diana; Hueso Kortekaas, Katia; Ibarra Marinas, Daniel; et al. (EDITUM. Ediciones de la Universidad de Murcia, 2025)
The aim of LIFE-SALINAS project has been to address some of the main preservation problems faced by the Regional Park of Las Salinas y Arenales de San Pedro del Pinatar, such as the erosion of the dunes of La Llana beach, the reduction of the optimal breeding area for waterfowl and the control of invasive alien species. This manual of good practices describes actions carried out to mitigate these problems, with the intention that they can serve as an example for actions in other similar areas.